Stable and Ordered Body‐Centered Cubic PdCu Phase for Highly Selective Hydrogenation (Small Methods 3/2023). Issue 3 (13th March 2023) - Li, Peicai; Liu, Xia; Guo, Mingrui; Pi, Yecan; Wang, Ning; Bai, Shuxing; Xu, Yong; Sun, Qi
Abstract : Inside Front Cover In article number 2201356, Pi, Bai, Xu, and co‐workers show that body‐centered cubic (bcc) PdCu can serve as selectivity controllers for selective hydrogenation of 3‐nitrostyrene. Product selectivity can be precisely adjusted by changing the hydrogen source. H2 dissociates to form *H on bcc‐PdCu, which preferentially reacts with CC to form 3‐nitro‐ethylbenzene with 93.8% selectivity. Bcc‐PdCu catalyzes the reaction of NH3 ·BH3 and –NO2 to produce 3‐amino‐styrene with 94.5% selectivity.